Rancang Bangun Sistem Inventarisasi Barang Berbasis Web dengan Integrasi Barcode dan QR Code untuk Meningkatkan Efisiensi Pengelolaan Stok (Studi Kasus: Toko Hassya Hijab) - Lulu Rachel Avisa; Rara Sriartati Redjeki (Jurnal JTIK (Jurnal Teknologi Informasi dan Komunikasi), 2026)
A web-based inventory system integrated with Barcode/QR Code technology was developed to enhance stock management at Hassya Hijab Store. The system, constructed using PHP and MySQL, facilitates centralized management of item data, suppliers, stock-in and stock-out transactions, reports, and user access rights based on specific roles. By incorporating Barcode/QR Code technology, the system significantly improves the speed and accuracy of item data recording and retrieval through code scanning, reducing reliance on manual data input and minimizing human error. Furthermore, the system allows for seamless integration between the inventory management process and real-time updates, ensuring data consistency across all transactions. Black-box testing revealed that essential functionalities such as managing master data, processing stock transactions, generating and scanning barcodes/QR codes, and producing automated reports operated as anticipated, confirming the system's reliability and performance. Based on these results, the system proves to be an efficient and effective solution for digital inventory management, making it highly suitable for use at Hassya Hijab Store, with potential for broader application in similar retail environments.